Kinetic Studies of Heterogeneous Reaction of HO2 Radical by Dicarboxylic Acid Particles. Issue 9 (24th July 2013) - Taketani, Fumiakzu; Kanaya, Yugo; Akimoto, Hajime
ABSTRACT The HO2 uptake coefficients (γ) for organic submicron aerosol particles were measured using an aerosol flow tube coupled with a chemical conversion/laser‐induced fluorescence technique under ambient conditions (760 Torr and 296 ± 2 K) and different values of relative humidity (RH) (28% and 68%). Determined uptake coefficients for succinic, glutaric, adipic, and pimelic acid aerosol particles at 28% RH were 0.07 ± 0.02, 0.07 ± 0.03, 0.02 ± 0.01, and 0.06 ± 0.03, respectively, whereas the γ values for those particles at 68% RH were 0.18 ± 0.07, 0.15 ± 0.04, 0.06 ± 0.01, and 0.13 ± 0.04, respectively. An increase in γ with increasing RH was observed for all the dicarboxylic acids, suggesting a contribution by water amount in the particle, aqueous phase chemistry, and uptake of HO2–H2O. The anomalously low γ values for adipic acid are likely related to its high crystallization RH and thus provide a new clue that the water amount and/or RH have a significant influence on HO2 uptake.